The role of invertebrates and aquatic fungi on the decomposition of eucalyptus leaves in streams - Mesquita, Ana (2004)
Resumo da comunicação apresentada no XII Congresso da Association Española de Limnología - IV Congresso Ibérico de Limnologia. CIMAR, Universidade do Porto, 5-9 Julho 2004.